Pengaruh Fitur Iklan, Promo Dan Interaksi Dengan Pelanggan Di Platfrom Whatsapp Bussiness Dalam Meningkatkan Volume Penjualan Di Nibras House - Noer Diana Fitriya; Moh Idil Ghufron (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of advertising features, promotions, and customer interactions through the WhatsApp Business platform on increasing sales volume at Nibras House, an MSME located in Alasnyiur Village, Besuk District. This research uses a descriptive quantitative approach with a saturated sampling technique, involving 31 respondents. Data were collected through closed questionnaires and analyzed using validity and reliability tests, descriptive statistics, and multiple linear regression with the help of Jamovi software. The results show that partially, only the advertising feature has a significant effect on increasing sales volume, while promotions and customer interactions do not have a significant effect. However, simultaneously, the three variables have a significant influence, with an R² value of 0.653. Therefore, the advertising feature on WhatsApp Business is proven to be effective in supporting the marketing strategy at Nibras House.